Contribution a l'etude des petits ruminants du Tchad - Dumas, R. (1980)
Describes the main sheep and goat breeds in Chad, based on the results of a survey on animal production and economics, 1977. Descriptions and data on ethnology, biometry, parameters and characteristics of reproduction, weight growth, and meat yield included. Observations indicated that the Fulani sheep reached a superior size as compared to the other breeds, but did not display high productivity rate in terms of precocity, reproduction parameters or meat output. The Mayo-Kebbi sheep, the tallest among south Chad sheep was outstanding by its reproduction qualities and meat output. The Kirdi goat, though small in size showed great prolificity rate and advantageous meat/carcass output.